Great Powers and Geopolitics: International Affairs in a Rebalancing World - Klieman, Aharon (Springer, 2015)
This book presents the theoretical-historical-comparative political framework needed to fully grasp the truly dynamic nature of 21st century global affairs. The author provides a realistic assessment of the shift from U.S predominance to a new mix of counterbalancing rival middle-tier and assertive regional powers, while highlighting those geopolitical zones of contention most critical for future international stability. The book will appeal to scholars and policy makers interested in understanding the contours of the emerging world order, and in identifying its principal shapers and leading political actors.